Zakat management and taxation - Abd Aziz Abu Bakar; Mohamad Amin Ibrahim; Shahizan Md Noh (IBFIM, 2014)
Financial planning consists of series of activities to reflect the comprehensive nature of the planning of individuals' state of financial affairs. Components of Islamic financial planning include zakat and taxation planning. In this book, fundamentals explanation on each of the components is provided. In addition, readers are exposed with the technical aspects of zakat and tax calculation and the correlation between the two components. We hope that this book will be a useful reference and a guide to students, including the practitioner, in financial planning and wealth management industry.